2017
DOI: 10.1007/s11695-017-2877-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a New Swallowable Intragastric Balloon Not Needing Endoscopy: Early Italian Experience

Abstract: The results of this study on 38 consecutive patients demonstrate that the Elipse™ Balloon is safe, effective, and very well accepted by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 12 publications
6
21
0
Order By: Relevance
“…In the first multi‐center prospective study of 34 patients by the same authors, Elipse demonstrated a TBWL of 10% at 4‐month follow‐up with additional improvements in HbA 1c , triglycerides, low density lipoprotein, and blood pressure 59 . Two additional studies demonstrated 11.6% TBWL at 4 months though decreased %TBWL at 12 months of 5.9% 60,61 …”
Section: Non‐fda Approved Gastric‐specific Devicesmentioning
confidence: 98%
“…In the first multi‐center prospective study of 34 patients by the same authors, Elipse demonstrated a TBWL of 10% at 4‐month follow‐up with additional improvements in HbA 1c , triglycerides, low density lipoprotein, and blood pressure 59 . Two additional studies demonstrated 11.6% TBWL at 4 months though decreased %TBWL at 12 months of 5.9% 60,61 …”
Section: Non‐fda Approved Gastric‐specific Devicesmentioning
confidence: 98%
“…In accordance with other studies, the EIGB inclusion criteria were as follows: body mass index (BMI) ≥ 27 kg/m 2 , and less than 45 kg/m 2 , and age between 18 and 65 years. Exclusion criteria included previous bariatric or gastric surgery, bowel obstruction, hiatal hernia >5 cm, heart failure, blood coagulation disorders, more than one other abdominal/ gynecological operation, certified pregnancy, eating disorders (bulimia, binge eating disorder, or night eating syndrome) [1][2][3][4][5][6], serum creatinine level greater than 1.8 mg/ dL or liver enzyme (glutamic oxaloacetic transaminase (GOT) or glutamic pyruvic transaminase (GPT)) levels less than three times the upper limit of normal [17], inability to comply with the LCKD or LCD for religious reasons, or the presence of chewing or swallowing disorders. After EIGB placement, the patients were randomized into two groups: the LCKD group that followed a LCKD and the LCD group that followed a standard LCD.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…Intragastric balloons have been used for weight loss (WL) in the last two decades, but the need for hospital recovery, upper GI endoscopy, and anesthesia is major limitations for this technique. The Elipse™ intragastric balloon (EIGB) is a new swallowable balloon that has no such limitations and has been proven to be safe, effective in achieving weight loss is also, and well tolerated by patients [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since some IFSO nations do not specify the type of endoluminal procedures performed, we cannot rule out the possibility that the number of Elipse placed in 2016 is underestimated. To the best of our knowledge, some authors reported a small series of patients without any significant complication [2][3][4][5]. However, a recent multicenter, prospective study [6] enrolling a larger population of 135 patients described 1 SBO (0.74%) that required a laparoscopic enterotomy.…”
mentioning
confidence: 99%